Exercise behaviors of persons with multiple sclerosis through the stepwise implementation lens of social cognitive theory. Issue 7 (26th March 2020) - Fifolt, Matthew; Richardson, Emma V.; Barstow, Elizabeth; Motl, Robert W.
Abstract: Background: Bandura has identified knowledge and four core determinants (e.g., self-efficacy, outcomes expectations, goals, and facilitators/impediments) along with a threefold stepwise implementation model for guiding health promotion and disease prevention interventions. Aims: This research explored the exercise behaviors of persons with multiple sclerosis (MS) through the articulated lens of social cognitive theory. Methods: We conducted secondary analysis of qualitative data from 50 people with MS using deductive, thematic analysis. Participant data were sorted into the three levels of Bandura's threefold stepwise implementation model using our collective perception of espoused beliefs regarding knowledge and the four core determinants of health promotion. Results: Participants expressed the four core determinants of health promotion and knowledge regarding exercise in different ways that permitted classification into distinct levels of Bandura's threefold stepwise implementation model. Conclusions: The confirmation of the four core determinants of health promotion and knowledge aligning with the threefold stepwise implementation model will allow better tailoring and targeting of exercise promotion interventions by healthcare providers, fitness professionals, and researchers. Implications for rehabilitation: Persons with multiple sclerosis (MS) are not as physically active as the general population of adults. There is substantial evidence of health benefits through exercise, yet lack of sufficient participation. Interventions for persons with MS in level 1 of Bandura's threefold stepwise implementation model should focus on maintenance of current exercise; technologies to track, record, and share exercise habits; information and guidance that is specific to individual symptoms; and updates on advancements in MS research. Interventions for persons with MS in level 2 of Bandura's threefold stepwise implementation model should raise awareness and understanding of the importance of exercise and overall health; motivational strategies; and low or no-cost options for exercise. Interventions for persons with MS in level 3 of Bandura's threefold stepwise implementation model should focus on establishing a connection between health and exercise; health communication; and incremental steps toward exercise.